A new Indian species of shoot and capsule borer of the genus Conogethes (Lepidoptera: Crambidae), feeding on cardamom - Shashank, P.r.; Kammar, Vasudev; Mally, Richard; Chakravarthy, A.k. (Zootaxa, 2018)
A new species, Conogethes sahyadriensis sp. nov. (Lepidoptera: Crambidae), feeding on cardamom, is described from India. The species status is supported by diagnostic morphology as well as by genetic data. A phylogenetic analysis based on the publicly available Conogethes COI barcode sequences finds C. sahyadriensis as sister to C. pluto, and it further reveals a number of clades that potentially represent additional undescribed species.The new species is delineated from closely related and superficially similar species of Conogethes.